Differential early response of monocyte/macrophage subsets to intra-operative corticosteroid administration in lung transplantation - Glorion, Matthieu; Pascale, Florentina; Huriet, Maxime; Estephan, Jérôme; Gouin, Carla; Urien, Céline; Bourge, Mickael; Egidy, Giorgia; Richard, Christophe; Gelin, Valérie; De Wolf, Julien; Le Guen, Morgan; et al. (Frontiers in Immunology, 2023)
Abbreviations: Lung transplantation (LT), ex vivo lung perfusion (EVLP), corticosteroids (CS), alveolar macrophages (AMs), monocytic cells (MoCs), dendritic cells (DCs), polymorphonuclear neutrophils (PMNs), ex vivo lung prefusion (EVLP), primary graft defect (PGD), carboxyfluorescein succinimidyl ester (CFSE), reverse transcription (RT), pulmonary artery (PA), pulmonary vein (PV), swine (sw), human (hu), broncho-alveolar lavage (BAL), untreated (UT), CS-treated (CST), isotype control (ISC), single cell RNA-seq (scRNA-seq), hematoxylin-eosin-saffron (HES).